Leachate Production Analysis and Arrangement of Gas Vent Pipelines in Ex-Landfill Sarbagita Regional Landfill - Gayatri, Putu Ari; Pandebesie, Ellina (IPTEK The Journal for Technology and Science, 2020)
Sarbagita Regional Landfill is a regional landfill which is located in Denpasar. At this time, there were closure and landfill arrangement in Sarbagita Regional Landfill. The utilization of ex-landfill land used as green open space requires leachate and gas handling due to the process of waste decomposition is still ongoing. Analysis of gas and leachate potential is needed for further management so that the surrounding environment is not polluted. Analysis of potential gas generation using a triangular method and analysis of leachate generation potential using the Thornwaite method. The maximum gas production occurs in 2023 at 43.367.678,25 m3/year. Gas production gradually declined until it’s estimated to run out in 2034. The number of gas pipe points needed is 19 points. Treatment methods that can be considered are the gas conversion to electricity method and the flaring method. The results of the calculation from leachate potential is 3.84 liters/second. The result will be used to planning a leachate processing installation. Processing system through 4 processing stages, namely processing in anaerobic ponds, facultative ponds, aerobic ponds, and biofilter ponds. Besides considering the technical aspects of technology selection, we also considered the Regional Government’s capability and commitment as the manager.